2017
DOI: 10.1002/2017jf004290
|View full text |Cite
|
Sign up to set email alerts
|

New Bedform Phase Diagrams and Discriminant Functions for Formative Conditions of Bedforms in Open‐Channel Flows

Abstract: Understanding of the formative conditions of fluvial bedforms is significant for both river management and geological studies. Diagrams showing bedform stability conditions have been widely used for the analyses of sedimentary structures. However, the use of discriminants to determine the boundaries of different bedforms regimes has not yet been explored. In this study, we use discriminant functions to describe formative conditions for a range of fluvial bedforms in a 3‐D dimensionless parametric space. We do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…3B. Finally, we validated the bedform stability diagram using a recent compilation of experimental and field data (46). We reduced this compilation to the range of Re p that span observations in the Torridonian Group, which resulted in 998 experimental data points and 47 field data points.…”
Section: [1]mentioning
confidence: 99%
“…3B. Finally, we validated the bedform stability diagram using a recent compilation of experimental and field data (46). We reduced this compilation to the range of Re p that span observations in the Torridonian Group, which resulted in 998 experimental data points and 47 field data points.…”
Section: [1]mentioning
confidence: 99%
“…First, the hydraulic conditions of plane bed regimes were examined with the sediment diameter and the sediment transport mechanism by which the sediment was moved, i.e., no sediment movement, bed-load, and suspended load. Bedform phases were expressed in the space of dimensionless parameters that reflected the properties of flows and sediment particles (Ohata et al, 2017;van den Berg & van Gelder, 1993). In this study, we employed the following dimensionless parameters to represent hydraulic conditions and sediment properties: the particle Reynolds number Re p , Shields number * , and the suspension index * s ⁄ .…”
Section: Data Sources and Dimensionless Parameters For Morphodynamic mentioning
confidence: 99%
“…Thus, bedform phase diagrams have been proposed based on laboratory and field observations (e.g., van den Berg & van Gelder, 1993). Recently, Ohata et al (2017) proposed bedform phase diagrams in three-dimensional parametric space, and their diagrams successfully reconstructed paleo-flow conditions from sedimentary structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, (Dorrell et al, 2011) suggested that poorly graded division in turbidites is a product of high-concentration suspension. However, analyses of the sedimentary structures only provide a range of flow conditions (Ohata et al, 2017), not the spatio-temporal development of flows.…”
Section: Introductionmentioning
confidence: 99%